ChemInform Abstract: Weak Arene C—H···O Hydrogen Bonding in Palladium‐Catalyzed Arylation and Vinylation of Lactones. Issue 43 (7th October 2013) - Huang, Zhiyan; Chen, Zuliang; Lim, Li Hui; Quang, Gia Chuong Phan; Hirao, Hajime; Zhou, Jianrong
Abstract A general method for the asymmetric synthesis of various α‐arylated lactones using chiral phosphine ligands is developed.